Genetic variability, heritability and character association studies for grain yield and yield attributing traits in segregating population of rice (Oryza staiva L.) - K. B. ESWARI, PARASHURAM PATROTI, M. SHESHU MADHAV. J. SURESH and (The Journal of Research, PJTSAU, 2017)
Thirty five leaf blast resistant BC1 F2 rice plants were evaluated for eleven morphological characters during kharif season, 2014 at Directorate of Rice Research (DRR), Hyderabad. Analysis of variance revealed significant differences among the genotypes for most of the traits. Phenotypic coefficients of variability were higher than genotypic coefficients of variability for all the traits. Phenotypic coefficient of variation ranged from 9.58-49.59, while genotypic coefficient of variation ranged from 9.51-54.90. High heritability was recorded in number of filled grains (97%) followed by spikelet fertility (86%), number of productive tillers/plant (56%). Genetic advance as percentage of mean ranged from 4.50 % (days to flowering) to 56.1% (number of filled grains/panicle). Plant yield showed positive and significant correlation with panicle weight (0.392) and spikelet fertility (0.817). Number of filled grains (1.166), number of tillers (1.101), plant height (0.351) and panicle weight (0.073) had positive direct effect on plant yield and unfilled grains with high negative direct effect (-1.043). The results indicated that for increasing rice yield with blast resistance, a genotype should possess more number of filled grains, number of tillers per plant, high spikelet fertility and large panicle size with medium plant height.